Rex the Runt - Season 2 Episode 1-13 - Sadler, Christopher; Fell, Sam; Peake, Peter (A&E, 2002)
Rex, Wendy, Bad Bob and Vince are four absurd clay dog creations experiencing the ups and downs, ins and outs, rounds and abouts of life, death, sex, the universe and seemingly everything else in between from the confines of their regular, everyday suburban home ... These four fun characters were created by animator Richard Goleszowski. He joined Bristol-based Aardman Animation in 1983, and began working on the likes of Morph and Peter Gabriel's "Sledgehammer" video. He has also brought us the award-winning frolics of "Robbie the Reindeer in Hooves of Fire". He's also directed Aardman's hugely-successful "Creature Comforts" series. [www.toonhound.com]
Keywords: DVD-Video